Early Kiwifruit Decline: A Soil-Borne Disease Syndrome or a Climate Change Effect on Plant–Soil Relations? - Bardi, Laura (Frontiers in Agronomy, 2020)
Kiwifruit early decline is a physiological disorder whose appearance was reported for the first time in New Zealand, following a cyclone that caused a heavy and prolonged flooding of kiwifruit orchards. Following studies on kiwifruit vine physiology and anatomy demonstrated that this plant has a significant water demand, but is also extremely sensible to roots waterlogging and soil anoxic conditions. Pathogenic microorganisms were sometimes identified in soil and root samples of declining plants, but they were not considered the primary cause of kiwifruit decline, and their presence in roots was considered a consequence of waterlogging and plant weakening. Agronomic practices have been developed and adopted to deliver water in amounts adequate to plant needs, but avoiding excess and stagnation in soil, and to improve soil aeration. However, in recent years early decline is spreading worldwide and is affecting even orchards in which waterlogging is prevented or is only occasionally caused by intense local rainfall. A global overview of the knowledge on botanical, physiological and ecological traits of kiwifruit, along with the examination of phenomena concomitant to early decline appearance, can help to identify the causes and the possible actions to prevent its occurrence. Some assumptions and possible solution attempts are proposed.